Happy birthday, Mallory! - Friedman, Laurie B., 1964-; Schmitz, Tamara (Minneapolis : Carolrhoda Books, 2005)
After a difficult year, Mallory plans a month-long celebration of her ninth birthday in hopes that her next year will be wonderful.
Keywords: Birthdays -- Fiction